Fetal double outlet right ventricle without heterotaxy syndrome: Diagnostic spectrum, associated extracardiac pathology and clinical outcomes. (27th June 2021) - Young, Aisling A.; McBrien, Angela; Caluseriu, Oana; Haberer, Kim; Wewala, Gayathri; Eckersley, Luke; Hornberger, Lisa K.
Abstract: Objectives: To document the clinical spectrum and outcomes of fetal double outlet right ventricle (DORV) without heterotaxy in a recent diagnostic era. Methods: Prenatal cases of DORV consecutively diagnosed from 2007 to 2018 were retrospectively identified. Clinical records, including details regarding genetic testing and pre and postnatal imaging were reviewed. Results: DORV was diagnosed in 99 fetuses without heterotaxy. The most common anatomic subtype was subaortic ventricular septal defect (VSD) and normally related great arteries with ( n  = 45, 45%) or without ( n  = 13, 13%) pulmonary stenosis. The remainder had a subpulmonic VSD with transposed great arteries ( n  = 15, 15%), atrioventricular valve atresia ( n  = 24, 24%), or remote VSD ( n  = 2, 2%). A genetic diagnosis was found in 32 (34%) of 93 tested. Major extracardiac anomalies were found in 40 (40%), including 17/24 (71%) with and 22/69 (32%) without an abnormal karyotype, with VACTERL association in 9. Genetic and/or extracardiac pathology was identified in 37/58 (64%) with a subaortic VSD, 5/15 (33%) with a subpulmonic VSD, 9/24 (38%) of those with AV valve atresia and 2/2 (100%) with a remote VSD. A genetic abnormality was a significant predictor of fetal demise (9/37 vs 1/62 p  < 0.01) or pregnancy termination (12/35 vs 9/64 p  = 0.03). Conclusions: Fetal DORV is associated with a high rate of genetic abnormalities and extracardiac pathology. The presence of genetic abnormalities impacts prenatal outcomes and parental decision‐making. Key points: What is already known about this topic? Fetal double outlet right ventricle (DORV) has been previously reported to be associated with genetic abnormalities in 14%–29%; however, most included cases of heterotaxy and were in an older era of genetic testing. What does this study add? In 99 cases of fetal DORV without heterotaxy encountered from 2007 to 2018, we found genetic diagnoses and/or extracardiac defects in 53% (genetic diagnoses in 34% of those tested).